Abandoned Pedways: Aftermaths of Spatial Design on the Perception of Insecurity [Calles Elevadas Abandonadas: Secuelas del Diseño Espacial en la Percepción de Inseguridad] - Hidalgo-Hermosilla, A; Martin-Quijada, R (Universidad de Chile, 2022)
Among the spatial devices for collective housing complexes designed by the Urban Improvement Corporation (CORMU) during the 1970s in Chile are the pedways to connect buildings and support the community experience. In most cases, this network has deteriorated, abandoned by the population that fears being a victim of crime in those places. Urban design theory has paid little attention to the relationship between spatial design and the perception of insecurity. Consequently, this study aims to determine how physical and spatial factors affect the perception of urban spaces as potentially unsafe. The qualitative methodology applied to the case study of the housing complex of “Parque Inés de Suárez” (Santiago 1971) is based on principles of the Situational Prevention Theory (CPTED); it considers the mapping of pedestrian routes, visual records, and interviews. The research suggests that the possibility of the occurrence of crimes depends on the degree of permeability of the spatial configuration and the absence of natural surveillance. The findings show that spatial configuration devices act as obstructions to movement and visual control, violating the cardinal principle of natural surveillance of the environment. According to this, the results suggest the need to update the practice of spatial design, integrating security as a constitutive factor of a healthy residential space. © 2022 Universidad de Chile. All rights reserved.